Hooked : how processed food became addictive - Moss, Michael, 1955- (WH Allen, 2021)
Everyone knows how hard it can be to maintain a healthy diet. But what if some of the decisions we make about what to eat are beyond our control? Is it possible that food is addictive, like drugs or alcohol? And to what extent does the food industry know, or care, about these vulnerabilities? In Hooked, Pulitzer Prize-winning investigative reporter Michael Moss sets out to answer these questions and to find the true peril in our food. Moss uses the latest research on addiction to uncover the shocking ways that food, in some cases, is even more addictive than alcohol, cigarettes, and drugs. Our bodies are hardwired for sweets, so food giants have developed fifty-six types of sugar to add to their products and ways to exploit our evolutionary preference for fast, ready-to-eat foods. Moss goes on to show how the processed food industry -- including major companies like Nestle, Mars, and Kellogg's -- has not only tried to hide the addictiveness of food but to actually exploit it. As obesity rates continue to climb, manufacturers are now claiming to add ingredients that can effortlessly cure our compulsive eating habits. A gripping account of the legal battles, insidious marketing campaigns, and cutting-edge food science that have brought us to our current public health crisis, Hooked lays out all that the food industry is doing to exploit and deepen our addictions, and shows us why what we eat has never mattered more.